(untitled) (Journal of the College of Education for Women, 2019)
This study deals with The Millstone (1965) which is a dramatic depiction of a singlemother heroine in a classic predicament. This novel is considered as representative of the agein which it was written. The primary theme is her intense preoccupation with questions offatalism and will. The work also involves, both explicitly and implicitly, feminist concerns.Because the central protagonist is a woman and the society in which she lives is depicted,accurately, as deeply patriarchal and class-bound, the problem of the individual’s capacity forself-determination is inevitably tied to the feminist perspective.